2021
DOI: 10.3390/pr9010105
|View full text |Cite
|
Sign up to set email alerts
|

Batch Mode Reactor for 3,5-Dinitrosalicylic Acid Degradation by Phanerochaete chrysosporium

Abstract: A new batch mode reactor was constructed to conduct continuous biodegradation of 3,5-dinitrosalicylic acid. Various types of matrices with immobilized Phanerochaete chrysosporium were immersed in a solution containing pollutant and mineral nutrients. Three parameters were chosen to optimize the process. The nitrate and nitrite ions concentrations and HPLC analysis were used to prove the biodegradation of 3,5-dinitrosalicylic acid, and the mixed effects model using one-factor ANOVA was used for statistical calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, the presence of a broad peak around 3500~3300 cm –1 contributing to O–H indicated that the PU coating exhibited a water absorption phenomenon. Moreover, the new weak peak at 1507 cm –1 contributing to a nitro group showed that 3, 5-dinitrosalicylic acid was secreted by P. chrysosporium as a by-product [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of a broad peak around 3500~3300 cm –1 contributing to O–H indicated that the PU coating exhibited a water absorption phenomenon. Moreover, the new weak peak at 1507 cm –1 contributing to a nitro group showed that 3, 5-dinitrosalicylic acid was secreted by P. chrysosporium as a by-product [ 39 ].…”
Section: Resultsmentioning
confidence: 99%